Achille Bonito Oliva and the Art System: The teoria di turno and the Art Contemporary Museums - Feo Rodríguez, Noemi María (Eikón / Imago, 2019)
In 1972 Achille Bonito Oliva defined the "art system" as a chain of San Antonio, constituted by the artist, the critic, the gallerist, the museum, the collector, the media and the public. In the nineties, this chain represented the basis of its current theory, a discourse in which globalization threatens the character of identity that leads to art, towards the homologation and the anorexia of the image. At the beginning of the 21st century, the Italian critic analyzed a plurality of functions, diverse and unprecedented, in the management and creation of museums, as the result of the redefinition of their theories. In 2004, in I fuochi dello sguardo: Musei che reclamano attenzione, Bonito Oliva establishes concepts, such as the collective literacy and the death of the public, which highlight the new models and challenges that contemporary art museums must face.